(untitled) (Journal of the College of Education for Women, 2019)
A computerized investigation has been carried out to design an immersion lenswith low aberration operating under zero magnification condition using inverse problem.The aberration is highly dependent on the shape of electrodes, for a preassigned electronbeam trajectory the paraxial-ray-equation is solved to determine the electrostatic potentialand field distribution.From the knowledge of the potential and its first and second derivative theelectron optical properties were computed, the electrode geometry was determined fromthe solution of Laplace equation.